The Influence of Return on Equity and Price Earnings Ratio on The Company Value of PT. Harum Energy Tbk: Period 2017-2021 - Arsifa, Nurul; Tansar, Indri Ayu (Electronic, Business, Management and Technology Journal, 2023)
This study aims to examine the impact of Return On Equity (ROE) and Price Earning Ratio (PER) on the valuation of PT. Harum Energy Tbk from 2017 to 2021. This study employs a quantitative methodology, focusing on the entire population of PT financial reports from Harum Energy Tbk. The sample was obtained through a time series approach by utilizing the company's quarterly financial data. Data collection is conducted by extracting information from the financial report paperwork that is publicly available on the official website of the Indonesia Stock Exchange (www.idx.co.id). The employed methodology is multiple regression analysis. The research findings indicate that Return On Equity has a significant positive impact on Company Value, as evidenced by a t-value of 3.583 and a significance value of 0.002, which is lower than the threshold of 0.05. The Price Earning Ratio has a notable positive impact on Company Value, as evidenced by a t-count of 4.275 and a significance value of 0.001, which is lower than the threshold of 0.05. In addition, both Return On Equity and Price Earning Ratio directly and significantly impact 54.9% on Company Value. This study offers a significant addition to comprehending the determinants that impact the value of a company, particularly at PT. Harum Energy Tbk. The findings of this study serve as a foundation for managerial and investor decision-making when assessing firm performance and investment opportunities. Key terms: Return On Equity, Price Earning Ratio, Company Value, PT. Harum Energy Tbk.